Pengaruh Customer Engangement Dan Electronic Word Of Mouth (E-WOM) Terhadap Keputusan Pembelian Di Urban Wagyu Steak House Surabaya (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2023)
This study aims to determine the effect of Customer Engagement and ElectronicWord of Mouth (E-WOM) on Purchase Decisions at Urban Wagyu Steak House Surabaya both simultaneously and partially as well as to determine variable that have a dominant influence on Purchase Decisions at Urban Wagyu Steak House Surabaya. This research is a quantitative research using multiple linear regression analysis method. The population in this study are Customers at Urban Wagyu Steak House Surabaya whose number is unknown. The sampling technique in this study is to use a simple random sampling technique or sampling taken by random and simple technique from the existing population. Based on the formula used to determine the sample, the number of samples are 100 people. Furthermore, the data were analyzed using the instrument test, classical assumption test, and multiple linear regression analysis. The results showed that Customer Engagement and Electronic Word Of Mouth (E-WOM) simultaneously had a significant positive effect on Purchase Decisions at Urban Wagyu Steak House Surabaya. Customer Engagement and ElectronicWord of Mouth (E-WOM) partially have a significant positive effect on Purchase Decisions at Urban Wagyu Steak House Surabaya. Electronic Word Of Mouth (E-WOM) has a dominant influence on Purchase Decisions at Urban Wagyu Steak House Surabaya, with a partial effect of 48,0%.